ARONIA MELANOCARPA (BLACK CHOKEBERRY) BRANCHES BIOMASS AS A SOURCE OF VALUABLE BIOLOGICALLY ACTIVE COMPOUNDS WITH ANTIOXIDANT AND ANTIMICROBIAL POTENTIAL (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
Aronia melanocarpa is a hardy berry-producing shrub that demands low maintenance and can grow on almost any type of soil. Since the best fruits can be obtained on the branches younger than 7 years, pruning of 1/3 of the shrub is usually performed each winter or after flowering, and also to remove damaged or overgrown branches. For sustainable production of Aronia melanocarpa berries, it is necessary to find a rational use for this pruning lignocellulosic biomass. Some studies available for Aronia melanocarpa berries show that they are very rich in various biologically active substances with proven functional and pharmacological activities including anti-inflammatory, antioxidant, and antimicrobial properties. The chemical composition of Aronia melanocarpa branches is currently almost unknown. The study aimed to evaluate the composition and potential of chokeberry branches as a source of polyphenols. General chemical characterization of the biomass was carried out using the method of analytical pyrolysis. Extraction of branch biomass was carried out using aqueous alcohol solutions. Quantitative analysis of the extracts showed a large amount of oligomeric proanthocyanidins. The most suitable extractant was determined to obtain the highest yield of the dominant polyphenols in the hydrophilic extract. The antioxidant activity of the hydrophilic extracts as well as antibacterial activity against six pathogenic bacteria was evaluated. The results showed the high potential of chokeberry lignocellulosic biomass as a source of valuable biologically active compounds for the creation of preparations for the healthcare, nutrition industry, and cosmetics.